EDITORIAL: A Bridge Across Time: 150 Years Since the Birth of Psychology as a Science (Studia Doctoralia Psychology and Educational Science, 2024)
The year 2024 marked the 150th anniversary of the founding of the first experimental psychology laboratory in Leipzig in 1879 by Wilhelm Wundt, widely recognized as the moment psychology emerged as a science. While 150 years ago, the names of the first "psychologists" were known among the elite scholars of the time, today the field of psychology boasts the highest employment growth rate compared to other occupations in the United States (Clay, 2014). In Romania, the number of certified practicing psychologists now exceeds 33,000. Despite the crisis Romanian psychology faced during the final decade of the communist regime, nearly 100 years after its inception in the country (Gruber, 1893), we now see unprecedented competition for admissions to psychologyfaculties. Meanwhile, across the Atlantic, approximately 6–6.5% of students choose psychology as their major, making it the most popular discipline within the fields of science and engineering.